Assessment of the heart displacement between prone and supine position on post mortem computed tomography (PMCT). (June 2020) - Loper, Nicole; O'Connor, Kate; Milne, David; Kesha, Kilak; Stables, Simon; Morrow, Paul; Glenn, Charley; Garland, Jack; Ondruschka, Benjamin; Tse, Rexson
Highlights: Post mortem body positions changes the heart position The heart generally displaces significantly anteriorly when the body is placed prone. The heart can displace up to 32.7 mm anteriorly at lateral left extent of heart at the level of the mid ventricle when placed prone The heart can also displace up to but also 14 mm at lateral left extent of heart at the level of the aorta when placed prone Post mortem position can be a confounding factor in measuring wound depths Abstract: Stab wounds are commonly encountered in forensic pathology practice and part of their examination and interpretation involves wound-depth measurements, which may provide information about the possible length of the implement. It is suggested that different body positions during life, such as leaning forward or standing up, may cause the internal organs to move relative to each other, and thus the stab wound depth in a non-supine position might be different when measured supine at post mortem examination. Whether internal organs move relatively in different post mortem positions is not well documented yet. This study documented significant post mortem anterior displacement of the heart when the body is prone compared to being supine, up to 32.7 mm. The displacement correlated negatively to weight and body mass index in certain locations, but not with age or height. This study provides evidence that when measuring a stab wound at post mortem examination, the position of the body can be a significant confounding factor affecting the accuracy of measurement and may have significant forensic relevance.